2009
DOI: 10.1088/0022-3727/42/6/065421
|View full text |Cite
|
Sign up to set email alerts
|

Morphological, optical and electrical properties of CdZnO films prepared by sol–gel method

Abstract: CdZnO films were deposited by the sol–gel spin coating method onto glass substrates. ZnO, Cd(0.25)Zn(0.75)O, Cd(0.50)Zn(0.50)O, Cd(0.75)Zn(0.25)O, CdO films were deposited using different rates of cadmium acetate dehydrate and zinc acetate dehydrate solutions. These values in parentheses refer to the ratio in solution. The dried and annealing temperatures were selected to be 300 °C and 500 °C in air, respectively. The XRD patterns show polycrystalline nature. It was observed that the crystal structure changes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
29
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(37 citation statements)
references
References 15 publications
6
29
0
Order By: Relevance
“…This confirms that the Cd doped ZnO thin films have significant light sensitive properties. Similar properties were reported by the Y. Caglar et al [19]. The electrical resistivity (ρ) of ZnO and Cd doped ZnO thin films have been measured in the temperature range of 300 to 500 K. The plots lnρ versus 1/T of ZnO and Cd doped ZnO thin films are shown in Fig.…”
Section: Electrical Conductivitysupporting
confidence: 83%
See 1 more Smart Citation
“…This confirms that the Cd doped ZnO thin films have significant light sensitive properties. Similar properties were reported by the Y. Caglar et al [19]. The electrical resistivity (ρ) of ZnO and Cd doped ZnO thin films have been measured in the temperature range of 300 to 500 K. The plots lnρ versus 1/T of ZnO and Cd doped ZnO thin films are shown in Fig.…”
Section: Electrical Conductivitysupporting
confidence: 83%
“…4 we have concluded two interesting things. Firstly, the pure ZnO fundamental absorption peak is observed at 372 nm i.e in UV region and as the doping concentration increases the peak is shifted towards higher wavelengths that is into a visible region, as reported by Y. Caglar et al [19]. Secondly, the band gap decreases on increasing the Cd concentrations.…”
Section: Optical Propertiessupporting
confidence: 51%
“…At a Fermi level distance, which is extremely remote from the particle center, the nuclear potential for the conduction of electrons is very low and therefore any transition with permitted quantum numbers will possess an absorption energy equal to the conduction band energy. 95 For comparison, the band gap values were decreased with increasing x values, as depicted in Table 3. It is considered that the increase in x value may result in an increase of defected states leading to an absorption coefficient increment.…”
Section: Band Gap Analysismentioning
confidence: 99%
“…Similarly to a TiO 2 photocatalyst, ZnO is also an ntype semiconductor with a wide band gap (~3.37 eV) and a large exciton binding energy (60 meV). Some studies have shown that the photoactivity of ZnO for the degradation of dyes is even better than that of TiO 2 [2,3,20]. Zinc oxide is a commercially available material that is relatively cheap, chemically stable and has low toxicity.…”
Section: Introductionmentioning
confidence: 99%